MULTIMODAL APPROACH TO DIAGNOSING POLYNEUROPATHIES OF VARIOUS ORIGINS IN CHILDREN - Gulomov Каххорали (International Journal of Scientific Pediatrics, 2025)
Background: Polyneuropathies in children pose diagnostic challenges due to their diverse etiologies, age-specific clinical presentations, and the need for specialized assessment techniques. A multimodal diagnostic approach, combining clinical evaluation, electrophysiology, laboratory studies, and imaging, is crucial for accurate diagnosis and management. Objective: To evaluate the effectiveness of a structured multimodal diagnostic approach in identifying pediatric polyneuropathies and determine the diagnostic yield of various modalities. Methods: A retrospective analysis was conducted on 85 pediatric patients (age range: 0-18 years) suspected of having polyneuropathy at Fergana Regional Children’s Multidisciplinary Medical Center. The diagnostic protocol included comprehensive clinical assessment, nerve conduction studies (NCS) and electromyography (EMG), targeted laboratory investigations, neuroimaging, and genetic testing when indicated. Results: Definitive diagnoses were established in 78 patients (91.8%). The most common etiologies were hereditary neuropathies (34.1%), immune-mediated inflammatory neuropathies (28.2%), and metabolic causes (15.3%). Nerve conduction studies had the highest diagnostic yield (89.4%), followed by targeted genetic testing (72.3% in hereditary cases) and laboratory investigations (68.2%). Conclusions: A structured multimodal approach significantly improves diagnostic accuracy in pediatric polyneuropathies. Early use of electrophysiological studies, combined with targeted laboratory and genetic testing, enables timely diagnosis and appropriate intervention.